United Arab Emirates Student Assessment : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
The United Arab Emirates has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component of efforts to improve education quality and learning outcomes as it provides the necessary information to meet stakeholders’ decision making needs. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, United Arab Emirates decided to benchmark this system using standardized tools developed under The World Bank’sSystems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The goal of SABER-Student Assessment is to promote stronger assessment systems that contribute to improved education quality and learning for all.